1996
DOI: 10.3109/02713689608997405
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan and chondroitin sulfate in rabbit tears

Abstract: The concentrations of hyaluronan (HA) and chondroitin sulfate (CS) in rabbit tears were determined using high performance liquid chromatography. The tears were taken from both normal eyes and eyes with a corneal epithelial defect. The concentration of CS was 7.61 times higher than that of HA in the tears of normal eyes. When the concentration of CS isomers was compared, the highest concentration was observed in chondroitin 6-sulfate (C6S), followed by chondroitin 4-sulfate (C4S) and chondroitin (C0S), in that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…Hyaluronic acid and chondroitin sulfate have recently demonstrated in rabbit tears using high performance liquid chromatography (MIYAUCHI et al, 1996). By the biotinylated hyaluronic acid binding region, we could not find any positive staining of hyaluronic acid in the acini and their lumen of the human lacrimal gland, although chondroitin sulfate immunoreactivity was distinctly detected in the secretory granules of acinar cells.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Hyaluronic acid and chondroitin sulfate have recently demonstrated in rabbit tears using high performance liquid chromatography (MIYAUCHI et al, 1996). By the biotinylated hyaluronic acid binding region, we could not find any positive staining of hyaluronic acid in the acini and their lumen of the human lacrimal gland, although chondroitin sulfate immunoreactivity was distinctly detected in the secretory granules of acinar cells.…”
Section: Discussionmentioning
confidence: 64%
“…Although the origin of hyaluronic acid in the corneal epithelium remains unknown, ASARI et al (1992b) have suggested that hyaluronic acid may be produced in the epithelial cells, since it is also localized in the limbal epithelial and skin epidermal layers (TAMMI et al, 1988;SORRELLI et al, 1990;ASARI et al, 1992b). Therefore, the hyaluronic acid in rabbit tears demonstrated by MIYAUCHI et al (1996) may not originate from the lacrimal gland but from the corneal epithelium. Of course, we cannot deny the possibility that hyaluronic acid is released from acinar or ductal cells in the lacrimal glands of humans as well rabbits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CS concentration in the tear fluid may change with corneal wound healing in rabbits [4,5] , and CS can be a factor that maintains corneal homeostasis. Investigating the changes in CS in human tear fluid after LASIK is useful not only for observing the wound-healing process, but also as an indicator of the clinical results.…”
Section: Discussionmentioning
confidence: 99%
“…HA plays an important role in tissue development, cell migration, cell proliferation and inflammation (Inoue and Katakami 1993, Gomes et al 2004). HA is increased in the tear fluid when corneal epithelium erosion is present, and may play an important role in corneal epithelium wound healing (Oya et al 1995, Miyauchi et al 1996. Tear fluid consistency (gel-like) can be attributed to HA (Itano et al 1999).…”
Section: Introductionmentioning
confidence: 99%